CircLDLR Promotes Papillary Thyroid Carcinoma Tumorigenicity by Regulating miR-637/LMO4 Axis. (9th December 2021) - Jiang, Yuan-ming; Liu, Wei; Jiang, Ling; Chang, Hongbin
Abstract : Background . Circular RNAs (circRNAs) have been reported to play important roles in the development and progression of papillary thyroid carcinoma (PTC). However, the function and molecular mechanism of circRNA low-density lipoprotein receptor (circLDLR) in the tumorigenesis of PTC remain unknown. Results . In this study, circLDLR was found to be markedly upregulated in PTC tissues and cell lines, and knockdown of circLDLR inhibited PTC cell proliferation, migration, and invasion but induced apoptosis in vitro . Moreover, circLDLR acted as a sponge for miR-637, and miR-637 interference reversed the anticancer effects of circLDLR knockdown on PTC cells. LMO4 was verified to be a target of miR-637; LMO4 upregulation abolished miR-637 mediated inhibition of cell growth and metastasis in PTC. Additionally, circLDLR could indirectly modulate LMO4 via acting as a sponge of miR-637 in PTC cells. Besides that, xenograft analysis showed that circLDLR knockdown suppressed tumor growth in vivo via regulating LMO4 and miR-637. Conclusion . Taken together, these results demonstrated that circLDLR promoted PTC tumorigenesis through miR-637/LMO4 axis, which may provide a novel insight into the understanding of PTC tumorigenesis and be useful in developing potential targets for PTC treatment.